2017
DOI: 10.14710/geoplanning.4.2.131-142
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing and Gis Approaches to a Qualitative Assessment of Soil Erosion Risk in Serang Watershed, Kulonprogo, Indonesia

Abstract: This research aims to determine the risk of soil erosion qualitatively byintegrating remote sensing with the geographic information system. Factors that contributed to the occurrence of erosion in the area of study were analyzed using the method of the variation of combined input data of the factors controlling erosion (soil, climate, topography, vegetation, and humans

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The north and western parts the study area is dominantly steep to very steep slopes that have the potential for erosion. Arif et al (2017) stated that the most influential factor on erosion in the Serang watershed in addition to erodibility is the topographic factors.…”
Section: Slopementioning
confidence: 99%
See 1 more Smart Citation
“…The north and western parts the study area is dominantly steep to very steep slopes that have the potential for erosion. Arif et al (2017) stated that the most influential factor on erosion in the Serang watershed in addition to erodibility is the topographic factors.…”
Section: Slopementioning
confidence: 99%
“…the heavy erosion classes that are justified as very heavy and moderate erosion classes because they exhibit the same erosion appearance in the field. However, the following erosion classes namely very light, light, and very heavy are easier because the boundaries between these erosion classes are very clearly marked (Arif et al, 2017). Justification for the erosion classes is very subjective based only on the combination of each of the two erosion parameters and the appearance of erosion encountered in the field, such as channel erosion, trench erosion, or root outcrop.…”
Section: Erosion Classmentioning
confidence: 99%
“…Research conducted by Wang et al (2013) showed that the use of Landsat TM satellite imagery provides up to 93% accuracy in erosion analysis compared to measurement results. Furthermore, Arif et al (2017) reported that the use of SPOT 5 satellite imagery provides up to 90.57% accuracy in estimating erosion in the Serang -Kulonprogo watershed.…”
Section: Introductionmentioning
confidence: 99%
“…It receives its water supply from the Serang River through the Pengasih Weir. The Serang Watershed is one of the most critical potential watersheds from a landform and land use perspective [28,29]. The slope length and steepness (LS) and soil erodibility (K) have contributed most to the erosion in the Serang Watershed [28].…”
Section: Introductionmentioning
confidence: 99%
“…The Serang Watershed is one of the most critical potential watersheds from a landform and land use perspective [28,29]. The slope length and steepness (LS) and soil erodibility (K) have contributed most to the erosion in the Serang Watershed [28]. The high level of erosion in the Serang watershed causes high sedimentation in the Pengasih irrigation scheme.…”
Section: Introductionmentioning
confidence: 99%